GW24-e1172 Fasudil restrain atrial fibrosis and its mechanism in a rat model of type 2 diabetes. (1st October 2013) - Chen, Jinling; Wu, Yongquan
Abstract : Objectives: This study was to investigate the role of RhoA/Rho kinase (ROCK) in atrial fibrosis in diabetic hearts, and the effects of fasudil hydrochloride hydrate on atrial fibrosis. Methods: A 8-week-old female Sprague-Dawley rat model of type 2 diabetes was established using high fat diet combined with streptozotocin (30 mg/kg, once, ip). Animals were randomly divided into 3 groups: control rats, untreated diabetic rats which received vehicle and treated diabetic rats that received Rho kinase inhibitor fasudil hydrochloride hydrate (10 mg·kg-1·d-1, ip, for 14 weeks). The morphological features of atrial fibrosis were observed using Masson staining. The mRNA expression of RhoA, ROCK-I, ROCK-II, type-I and type-III procollagen were assessed with RT-PCR. The protein levels of RhoA, ROCK-I, ROCK-II were evaluated using Western blotting. Results: The atria of untreated diabetic rats showed remarkable atrial fibrosis as compared to the control rats, the mRNA expression levels of type-I and type-III procollagen were increased, the mRNA and protein expression levels of RhoA, ROCK-I, ROCK-II were upregulated. The treatment with fasudil hydrochloride hydrate significantly relieved atrial fibrosis, the mRNA expression levels of type-I and type-III procollagen were reduced, the mRNA and protein expression levels of RhoA, ROCK-I, ROCK-II were decreased. Conclusions: The data suggest that RhoA/ROCK is involved in atrial fibrosis and fasudil hydrochloride hydrate ameliorates atrial fibrosis in rats with type 2 diabetes.